Distal femur periprosthetic knee fractures in elderly patients: clinical and radiographic outcome after internal fixation - Canton, Gianluca; Tomic, Marko; Giunta, Michele; Maritan, Guido; Murena, Luigi (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work: The incidence of periprosthetic knee fractures is steadily increasing, especially in the geriatric population. Surgical treatment in these patients must consider the poor bone quality and the risks of general complications related to age and comorbidities. The aim of the present study is to analyze the clinical and radiographic outcome of internal fixation for periprosthetic knee fractures of the distal femur in elderly patients (>75aa). Methods: All patients treated at the Orthopedic and Traumatology Unit of Cattinara Hospital-ASUGI (Trieste, Italy) between September 2014 and September 2019 for distal femur periprosthetic fracture after total knee replacement were included in the study. Mortality, complications, radiographic healing and functional outcomes were retrospectively evaluated. Data collection was conducted by clinical database searching and telephone interview. Results were compared with the literature. Results: The study population included 19 patients, F:M 16:3, mean age 84 years. Plate fixation was used in the majority of cases (90%). One-year mortality was 21.05%. Radiographic healing of the fracture occurred in 92% of cases. Nonetheless, 61% of patients saw a worsening in their functional outcome. Conclusion: Internal fixation is a valuable and safe option for distal femur periprosthetic fracture treatment in the elderly. The significant impact of periprosthetic knee fractures on the medium- to long-term survival and quality of life of the elderly patient is confirmed.